Genetic polymorphism of ALDH2 in Indonesia’s Minang ethnic - Abdul Halim Sadikin; Irene Dian; Mukharjon Mukharjon; Rini Puspitaningtum; Septelia Inawati Wanandi (Indonesian Society for Biochemistry and Molecular Biology, 2021)
Background: In some people, acetaldehyde, a toxic product from ethanol oxidation, cannot be oxidized to acetate. The excess of acetaldehyde could cause facial flushing, dizziness, and hypertension when they consume ethanol. This ethanol sensitivity is caused by a deficiency of ALDH2. Objective: This study aims to analyze and count the polymorphism frequency of the ALDH2 gene in Indonesia’s Minang ethnic. Methods: DNA samples were taken randomly from hair bulbous of 60 subjects (male and female, 3rd generation). A nested polymerase chain reaction was conducted to amplify the ALDH2 in the samples. Afterward, restriction fragment length polymorphism (RFLP) was conducted to the amplicons using the EcoRI restriction enzyme. The measured parameters were the distribution of the wildtype, atypical homozygote, and heterozygote. Results: Results showed that out of 60 subjects, 53.33% have an atypical homozygote gene (subjects prone to hypersensitive to alcohol), 28.33% have a heterozygote gene, and 18.33% have a wildtype gene. The frequency of the atypical alleles in Minang ethnic is 0.675. Conclusion: The atypical ALDH2 allele was much higher than the normal ALDH2 allele, in which most participants have atypical homozygote ALDH2, suggesting the samples are sensitive to alcohol.